Pengaruh Digital Marketing dan Desain Produk terhadap Kepuasan Konsumen dengan Keputusan Pembelian sebagai Variabel Intervening - Rifandi Septianta; Henny Welsa; Nonik Kusuma Ningrum (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine the effect of digital marketing and product design on consumer satisfaction with purchase decisions as a variable (a case study on consumers of Aerostreet products in the city of Yogyakarta). The population used in this study are consumers of Aerostreet products. This study uses a quantitative approach, using the technique of Non-Probability Sampling and purposive sampling approach with a total sample of 151 respondents. The data in this study were taken using a questionnaire via Google form for consumers of Aerostreet products. After all the data was collected, the data was tabulated using MS Excel and analyzed using SPSS version 25. The results of this study indicate that Digital Marketing (DP) has not effect on Purchase Decisions (KP). Product Design (DP) has a positive and significant effect on Purchase Decisions (KP). Purchase Decision (KP) has a positive and significant effect on Consumer Satisfaction (KK). Digital Marketing (DP) has a positive and significant effect on Consumer Satisfaction (KK). Product Design (DP) has a positive and significant effect on Consumer Satisfaction (KK). The influence of Digital Marketing (DM) on Consumer Satisfaction (KK) through Purchase Decision (KP) as an intervening variable is rejected. The effect of Product Design (DP) on Consumer Satisfaction (KK) through Purchase Decision (KP) as an accepted intervening variable. Keywords: Digital Marketing; Product Design; Purchase Decision; Customer Satisfaction